Implementasi Kedaulatan Permanen atas Sumber Daya Alam Dalam Aturan Investasi Asing di Aljazair dan Indonesia - Saru Arifin (Fakultas Hukum Universitas Islam Indonesia, 2018)
Since first coined by the United Nations at the end of 1950’s, the doctrine of permanent sovereignty over natural resources has experienced rapid dynamics of development — from those originally traditionally practiced to the national interests of a country — then developed and intersected various global issues, such as economy, environment, human rights, and climate change. Such doctrine only confirms to the countries of the world about the importance of permanent sovereignty for each country over its natural resources. However, the management needs to pay attention to various important aspects that intersect with human interests universally and inclusively. This study uses a normative legal method to discuss the implementation of the 1950 state sovereignty doctrine over natural resources in the investment legal system of developing countries such as Africa and also Indonesia, which is actively opening up to local and international investors to improve the national economy for social welfare. The results show that the implementation of UN Resolution on permanent sovereignty of natural resources in the practice of foreign investment in Algeria is limitative, particularly towards strategic naturalresources. In contrast, the practice of foreign investment in Indonesia is liberal in nature, and even its share ownership can reach one hundred percent.